Catalyst carrier, preparation method thereof, catalyst containing catalyst carrier and application of catalyst carrier in hydrotreatment of inferior wax oil

By using titanium-aluminum composite oxide and Ti-doped Y molecular sieve as catalyst support, the dispersion of acid center and active metal is adjusted, and the problem of low nitride removal efficiency of existing catalysts is solved, and the functions of hydrogenation and hydrogenation are realized The matching significantly improves the nitride removal rate in inferior wax oils.

CN119303617APending Publication Date: 2025-01-14CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411400158.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing hydrotreating catalysts are inefficient in removing nitrides from heavy oil, resulting in carbon accumulation or poisoning inactivation during catalytic cracking and hydrocracking, affecting product yield and quality.

Method used

The Y molecular sieve doped with titanium-aluminum composite oxide and Ti-doped Y molecular sieve is used as the catalyst support. By adjusting the number of acid centers and the dispersion of active metals, the matching of hydrogenation and hydrogenolysis functions is achieved, and the catalyst's deep removal ability of nitrides is improved.

Benefits of technology

The denitrification activity is significantly improved in the hydrotreatment of inferior wax oil, taking into account the hydrogenation and hydrogenolysis activity of the catalyst, and improving the deep removal rate of nitride in heavy oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303617A_ABST
    Figure CN119303617A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst carrier, a preparation method thereof, a catalyst containing the catalyst carrier and application of the catalyst carrier in hydrotreatment of inferior wax oil. The catalyst carrier comprises a titanium-aluminum composite oxide and a Ti-doped Y molecular sieve, the weight ratio of the titanium-aluminum composite oxide to the Ti-doped Y molecular sieve is (9: 1)-(6: 4). On the basis, the catalyst has good hydrogenation and hydrogenolysis function matching performance, and can show relatively high denitrification activity in hydrotreatment of inferior wax oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst carrier and a preparation method thereof, a catalyst containing the same and application of the catalyst in hydrogenation treatment of inferior wax oil, belonging to the technical field of catalyst preparation. Background Art

[0002] The efficient and low-carbon conversion of low-quality heavy oil into clean light oil products and high-value-added chemical raw materials is a necessary measure to achieve high-quality transformation and development of the petrochemical industry. Hydroprocessing technology can effectively remove heteroatoms such as sulfur, nitrogen, metals and polycyclic aromatic hydrocarbons from heavy oil, provide raw materials for subsequent catalytic cracking and hydrocracking processes, and thus realize the transformation of low-quality heavy oil into light oil products and chemical raw materials.

[0003] The removal rate of existing hydroprocessing catalysts for sulfides and metal compounds is generally high (more than 90%), but the removal rate for nitrides is very low (usually only about 60%). The presence of nitrides is very unfavorable to processes such as catalytic cracking and hydrocracking, and it is easy to cause carbon deposition or poisoning and deactivation of cracking catalysts, resulting in low yield and poor quality of target products. Therefore, deep hydrodenitrogenation of heavy oil is very necessary. Studies have shown that nitrides first need to undergo hydrogenation saturation reactions of aromatic rings or nitrogen heterocycles during the hydroprocessing process, and then undergo CN bond breaking reactions, which requires that the hydrogenation catalyst should have both good hydrogenation performance and hydrogenolysis performance.

[0004] CN106925287A discloses a hydrogenation catalyst with titanium oxide-modified silicon-aluminum composite oxide as a carrier and Group VIB and Group VIII metals as active components. The carrier has the characteristics of gradient pore distribution, large specific surface area, large pore volume, etc., so the active components can be evenly dispersed on the carrier surface, but excessive dispersion of active metals will lead to a decrease in the number of active phase stacking layers after sulfidation, which is not conducive to the adsorption and hydrogenation reaction of nitride molecules.

[0005] CN114643070B discloses a catalyst that can be used for heavy oil hydrodenitrogenation and a preparation method thereof. The catalyst is composed of a carrier, an active metal, phosphomolybdenum blue, an electronic auxiliary agent and a surfactant. Compared with the hydrogenation catalyst prepared by the conventional method, the catalyst exhibits a higher active phase crystal length and stacking layer number and a higher metal utilization rate, so that the hydrogenation activity of the catalyst is improved to a certain extent. However, the catalyst does not have a very high removal rate for nitrides in heavy oil, and fails to fully achieve the purpose of deep denitrification, which may be related to its lack of hydrogenolysis performance.

[0006] Existing hydroprocessing catalysts fail to take into account the appropriate interaction between the active metal and the carrier and the appropriate The number of acid centers results in a mismatch between the hydrogenation activity and the hydrogenolysis activity of the catalyst, which hinders the catalyst from deeply removing nitrogen compounds from heavy oil. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a catalyst carrier and a preparation method thereof, a catalyst containing the same and its application in the hydrotreatment of inferior wax oil, the catalyst achieves the matching of hydrogenation and hydrogenolysis functions, and can show higher denitrification activity in the hydrotreatment of inferior wax oil.

[0008] To achieve the above object, the present invention provides a catalyst carrier, which includes titanium aluminum composite oxide and Ti-doped Y molecular sieve; and the weight ratio of titanium aluminum composite oxide to Ti-doped Y molecular sieve is 9:1 to 6:4.

[0009] In some optional embodiments, the weight ratio of the titanium aluminum composite oxide to the Ti-doped Y molecular sieve may be 9:1, 8:2, 7:3 or 6:4.

[0010] Compared with the traditional industrial catalyst formed by γ-Al2O3-based catalyst carrier, the catalyst carrier provided by the present invention can enable the catalyst to have both excellent hydrogenation activity and hydrogenolysis activity in the subsequent application in the catalyst, thereby achieving the matching of hydrogenation function and hydrogenolysis function, and can show higher denitrification activity in the subsequent hydrogenation treatment of inferior wax oil.

[0011] On the one hand, the present invention significantly improves the subsequent catalyst by doping Y molecular sieve into the aluminum-based oxide carrier. On the other hand, the present invention reduces the number of strong Lewis acid centers (LAS) on the surface of aluminum-based oxides and Y molecular sieves by Ti doping, reduces the strong interaction between active metals and carriers, improves the dispersibility and sulfidation degree of active metals in subsequent catalysts, and the number of stacking layers of active phases, and promotes the adsorption and hydrogenation reaction of nitrogen-containing compound molecules. In particular, the weight ratio of titanium aluminum composite oxide and Ti-doped Y molecular sieve is 9:1 to 6:4, which can better enable the catalyst to take into account both the appropriate interaction between active metals and carriers and the appropriate The number of acid centers can be increased, thereby making the hydrogenation activity of the catalyst better matched with the hydrogenolysis activity, thereby improving the catalyst's deep removal of nitrogen compounds from heavy oil.

[0012] Furthermore, in the Ti-doped Y molecular sieve, the molar ratio of TiO2 / Al2O3 is 0.05 to 0.2:1 in the form of TiO2 and Al2O3.

[0013] Furthermore, in the titanium aluminum composite oxide, the molar ratio of TiO2 / Al2O3 is 0.5 to 2:1 in the form of TiO2 and Al2O3.

[0014] The present invention also provides a method for preparing the aforementioned catalyst carrier, which comprises: mixing titanium aluminum composite oxide, Ti-doped Y molecular sieve, binder, nitric acid and deionized water, and then sequentially performing molding (such as extrusion molding), first aging, first drying and first calcination to obtain a catalyst carrier.

[0015] Furthermore, the amount of the binder is 1-5wt%, preferably 2-4wt%, of the total weight of the titanium-aluminum composite oxide and the Ti-doped Y molecular sieve. The type of the binder is not particularly limited, and can be one or a combination of two or more of sesbania powder, polyvinyl pyrrolidone and aminotrimethylenephosphonic acid.

[0016] Furthermore, the first drying temperature is 50-120° C. and the time is 2-8 hours; the first calcination temperature is 450-600° C. and the time is 2-6 hours.

[0017] Furthermore, the amount of nitric acid used accounts for 0.2-1 wt% of the total weight of the titanium-aluminum composite oxide and the Ti-doped Y molecular sieve.

[0018] Furthermore, the catalyst carrier having a size of 20 to 40 meshes can be obtained by crushing and sieving.

[0019] In a preferred embodiment, titanium-aluminum composite oxide is prepared by the following steps: adding ammonia water to the first aluminum source aqueous solution until the pH of the system is 7-8, then adding a titanium-aluminum co-solution containing the first titanium source and the second aluminum source to the system for reaction, and controlling the pH during the reaction to be 7-8 to obtain a sol system; allowing the sol system to stand, first filter, first wash, second dry, and second calcinate in sequence to obtain a titanium-aluminum composite oxide.

[0020] Furthermore, the first aluminum source and the second aluminum source are each independently selected from one or a combination of two or more of aluminum nitrate, aluminum isopropoxide and aluminum sulfate, and the first titanium source is selected from one or a combination of two or more of titanium sulfate, titanium isopropoxide, tetrabutyl titanate and titanium tetrachloride.

[0021] Furthermore, the second drying process is performed at a temperature of 80 to 140° C. and a processing time of 2 to 10 hours; the second calcination process is performed at a temperature of 500 to 600° C. and a processing time of 2 to 8 hours.

[0022] Furthermore, the Ti-doped Y molecular sieve is prepared by the following steps: mixing a third aluminum source, a first silicon source, a first metal mineralizer and deionized water to obtain a guiding agent; first mixing the guiding agent, the second metal mineralizer and the second silicon source, and then adding a dispersion containing a fourth aluminum source and a third metal mineralizer to the system, and then adding a fifth aluminum source and a second titanium source to the system to mix to obtain a primary gel; subjecting the primary gel to a second aging and a first crystallization in sequence to obtain a secondary gel; then mixing the secondary gel, the third metal mineralizer and the third silicon source and subjecting the secondary gel to a second crystallization, a second filtration, a second washing, a third drying and a third calcination in sequence to obtain a primary molecular sieve; mixing ammonium nitrate and the primary molecular sieve and subjecting the same to a third crystallization, a third filtration, a third washing, a fourth drying and a fourth calcination in sequence to obtain a Ti-doped Y molecular sieve.

[0023] Furthermore, the third aluminum source, the fourth aluminum source and the fifth aluminum source are each independently selected from one or a combination of two or more of sodium aluminate, aluminum sulfate and aluminum nitrate.

[0024] Further, the second silicon source and the third silicon source are each independently selected from one or a combination of two or more of silica sol, water glass and tetraethyl orthosilicate (TEOS).

[0025] Further, the first metal mineralizer, the second metal mineralizer, the third metal mineralizer and the fourth metal mineralizer are each independently selected from potassium hydroxide and / or sodium hydroxide.

[0026] Furthermore, the second titanium source is selected from one or a combination of two or more of titanium sulfate, titanium isopropoxide, tetrabutyl titanate and titanium tetrachloride.

[0027] Furthermore, the first crystallization process temperature is 50-80° C. and the time is 20-30 hours.

[0028] Furthermore, the second crystallization is a step-by-step temperature crystallization: first, crystallize at 50-80°C for 8-16h, then crystallize at 80-100°C for 20-30h, and finally crystallize at 100-120°C for 2-8h.

[0029] Furthermore, the third crystallization process is performed at a temperature of 80 to 100° C. and for a time of 2 to 6 hours.

[0030] Furthermore, the third drying process has a treatment temperature of 100 to 140° C. and a treatment time of 2 to 10 hours; the third calcination process has a treatment temperature of 500 to 600° C. and a treatment time of 2 to 8 hours.

[0031] Furthermore, the fourth drying process has a treatment temperature of 100 to 140° C. and a treatment time of 2 to 10 hours; the fourth calcination process has a treatment temperature of 500 to 600° C. and a treatment time of 2 to 8 hours.

[0032] The present invention provides a catalyst, which comprises the above-mentioned catalyst carrier and an active metal component supported on the catalyst carrier.

[0033] Based on the reasons mentioned above, the catalyst contains a large number of hydrogenation and hydrogenolysis active centers at the same time, and achieves the matching of hydrogenation and hydrogenolysis functions, and can show high denitrification activity in the hydrogenation treatment of inferior wax oil.

[0034] Furthermore, based on 100% of the catalyst, the loading amount of the active metal component is 10 to 30 wt%.

[0035] Preferably, the active metal component is selected from Group VIB metal elements and / or Group VIII metal elements. More preferably, the Group VIB active metal element is W, and the Group VIII active metal element is Ni; based on the mass of oxides, WO3 accounts for 16-20wt% of the catalyst, and NiO accounts for 2-6wt% of the catalyst.

[0036] In an optional embodiment, the above catalyst can be prepared by the following steps: using an equal volume co-impregnation method to load the active metal of Group VIB and / or Group VIII on the surface of the above catalyst carrier, and aging, drying and calcining to obtain a hydrogenation catalyst. Wherein, the drying temperature is 50-120°C and the time is 2-8 hours; the calcination temperature is 450-600°C and the time is 2-6 hours.

[0037] The present invention provides an application of the above catalyst in the hydrogenation treatment of inferior wax oil.

[0038] In an optional embodiment, when the coker gas oil is hydrotreated, a fixed bed process is used, the reaction temperature is 320-420°C, the hydrogen partial pressure is 2-12 MPa, the hydrogen-oil volume ratio is 300-1000:1, and the liquid hourly space velocity is 0.1-1.5 h -1 .

[0039] Before the coking gas oil is subjected to hydrogenation treatment, the above-mentioned catalyst can be pre-sulfurized. The sulfiding liquid is a cyclohexane solution containing 1-5 wt% carbon disulfide; the sulfiding method adopts a high-low temperature sulfidation method: first sulfiding at 300-360°C for 2h, then sulfiding at 320-380°C for 4h, and the hydrogen partial pressure and liquid hourly space velocity remain unchanged, which are 2-6MPa and 2-8h respectively. -1 .

[0040] Based on the above reasons, the catalyst of the present invention contains more hydrogenation and hydrogenolysis active centers at the same time, and achieves the matching of hydrogenation and hydrogenolysis functions, and exhibits higher denitrification activity in the hydrogenation treatment of inferior wax oil. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1The XRD spectrum of the titanium-aluminum composite oxide in Example 1 of the present invention is shown;

[0042] Figure 2 The XRD spectrum of the Ti-doped Y molecular sieve in Example 2 of the present invention is shown. DETAILED DESCRIPTION

[0043] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0044] It is explained that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the data used in this way can be interchanged in appropriate circumstances, so that the embodiments of the present application described here. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0045] (I) Preparation of catalyst carrier

[0046] Example 1

[0047] This embodiment provides a method for preparing titanium aluminum composite oxide (TiO2-Al2O3) by pre-hydrolysis-coprecipitation method, comprising the following steps:

[0048] 1. Dissolve 37.5 g aluminum nitrate nonahydrate (i.e., the second aluminum source) and 24.0 g titanium sulfate (i.e., the first titanium source) in 1 L of deionized water to prepare 0.1 mol·L -1 The aluminum nitrate aqueous solution and the titanium sulfate aqueous solution are then mixed evenly to obtain a titanium-aluminum co-solution.

[0049] 2. Weigh 37.5 g of aluminum nitrate nonahydrate (i.e., the first aluminum source) and dissolve it in 1 L of deionized water to prepare 0.1 mol·L -1 To the first aluminum source aqueous solution, an appropriate amount of dilute ammonia water (mass concentration 22.5wt%) is added dropwise at 50°C under continuous stirring until the pH value is 7-8, and then the above-mentioned titanium aluminum co-solution and an appropriate amount of dilute ammonia water (mass concentration 22.5wt%) are added dropwise to form a sol system. During this period, the pH value of the sol system needs to be maintained at 7-8.

[0050] 3. The above sol system was stirred for 0.5 h and then allowed to stand for 2 h, then cooled to room temperature for reduced pressure filtration (i.e., the first filtration) and washing operations (i.e., the first washing), and then the solid product was placed in an oven at 120°C for 4 h (i.e., the second drying), and finally the dried product was calcined at 550°C for 4 h (i.e., the second calcination) to obtain a TiO2-Al2O3 composite oxide (in the form of TiO2 and Al2O3) with a titanium-aluminum molar ratio of 1:1, recorded as TA.

[0051] Figure 1 This is the XRD spectrum of the titanium-aluminum composite oxide in Example 1.

[0052] Example 2

[0053] This embodiment provides a method for preparing a Ti-doped Y molecular sieve carrier, comprising the following steps:

[0054] 1. Weigh 0.74 g of sodium aluminate (i.e., the third aluminum source) and 5.34 g of sodium hydroxide (i.e., the first metal mineralizer) and dissolve them in 17 mL of deionized water and stir until they are translucent. Then add 13 g of silica sol (i.e., the first silicon source) and continue stirring for 2 h. After standing for 20 h, a directing agent is obtained.

[0055] 2. Weigh 2g of sodium hydroxide (i.e., the second metal mineralizer) and dissolve it in 70mL of deionized water and stir evenly. Then add 150g of water glass (i.e., the second silicon source) and continue stirring for 0.5h. Then transfer it to a 10-15℃ water bath reactor and add the above-mentioned directing agent dropwise under continuous stirring. Then add the dispersion composed of 7.5g of sodium aluminate (i.e., the fourth aluminum source), 2g of sodium hydroxide (i.e., the third metal mineralizer) and 40mL of deionized water prepared in advance and continue stirring for 0.5h. Then add 200mL of 0.1mol·L -1 Aluminum sulfate solution (the fifth aluminum source) and 70 mL 0.1 mol·L -1 of titanium sulfate solution (i.e., the second titanium source) and continued stirring for 2 h to obtain a primary gel.

[0056] 3. The primary gel was placed in a crystallization kettle and aged in an oven at 30°C for 24 hours (i.e., the second aging), and then transferred to an oven at 60°C for crystallization for 24 hours (i.e., the first crystallization) to obtain a secondary gel.

[0057] 4. Take out the above secondary gel and cool it to room temperature, weigh 2g of sodium hydroxide (i.e., the fourth metal mineralizer) and dissolve it in 40g of deionized water, stir for 5 to 15min, add 20mL of ethyl orthosilicate (i.e., the third silicon source), and then add the above cooled secondary gel, continue stirring for 1h, then transfer to a crystallization kettle and crystallize in an oven at 60°C for 12h, then in an oven at 90°C for 24h, and finally in an oven at 110°C for 4h (i.e., the second crystallization).

[0058] 5. Take out the above-mentioned second crystallization product for reduced pressure filtration (i.e., second filtration) and washing operation (i.e., second washing), then place it in a 120°C oven for drying for 4 hours (i.e., third drying), and finally calcine the dried product at 550°C for 4 hours (i.e., third calcination) to obtain a Ti-modified NaY type molecular sieve (i.e., primary molecular sieve).

[0059] 6. Weigh 0.8g of ammonium nitrate and dissolve it in 100g of deionized water. After stirring evenly, transfer it to a 60℃ water bath reactor. Gradually add 10g of the above Ti-modified NaY molecular sieve (i.e., primary molecular sieve) under continuous stirring. Continue stirring for 2h and transfer it to a crystallization kettle for crystallization in a 90℃ oven for 4h (i.e., the third crystallization). Then perform vacuum filtration (i.e., the third filtration) and washing operation (i.e., the third washing). Then dry it in a 120℃ oven for 4h (i.e., the fourth drying). Finally, calcine it in a 550℃ muffle furnace for 4h (i.e., the fourth calcination) to obtain a primary ammonium exchanged Y molecular sieve. Repeat the above steps 3 times to obtain a Ti-doped Y molecular sieve carrier (in the form of TiO2 and Al2O3) with a titanium-aluminum ratio of 0.1:1, which is recorded as TY.

[0060] Figure 2 This is the XRD spectrum of the Ti-doped Y molecular sieve in Example 2 of the present invention.

[0061] Example 3

[0062] This embodiment provides a method for preparing a catalyst carrier, comprising the following steps:

[0063] The TiO2-Al2O3 composite oxide in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 9:1, and then 2.5 wt% of sesbania powder, 0.5 wt% of nitric acid and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h (i.e., the first aging), and then dried in an oven at 120°C for 4 h (i.e., the first drying), and finally calcined in a muffle furnace at 550°C for 4 h (i.e., the first calcination) to obtain a catalyst carrier, recorded as TATY1.

[0064] Example 4

[0065] This embodiment provides a method for preparing a catalyst carrier, comprising the following steps:

[0066] The TiO2-Al2O3 composite oxide carrier in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 8:2, and then 2.5 wt% of sesbania powder by weight of the carrier, 0.5 wt% of nitric acid by weight of the carrier and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h, and then dried in an oven at 120°C for 4 h, and finally calcined in a muffle furnace at 550°C for 4 h to obtain a catalyst carrier, recorded as TATY2.

[0067] Example 5

[0068] This embodiment provides a method for preparing a catalyst carrier, comprising the following steps:

[0069] The TiO2-Al2O3 composite oxide carrier in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 7:3, and then 2.5 wt% of sesbania powder by weight of the carrier, 0.5 wt% of nitric acid by weight of the carrier and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h, then dried in an oven at 120°C for 4 h, and finally calcined in a muffle furnace at 550°C for 4 h to obtain a catalyst carrier, recorded as TATY3.

[0070] Example 6

[0071] This embodiment provides a method for preparing a catalyst carrier, comprising the following steps:

[0072] The TiO2-Al2O3 composite oxide carrier in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 6:4, and then 2.5 wt% of sesbania powder by weight of the carrier, 0.5 wt% of nitric acid by weight of the carrier and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h, then dried in an oven at 120°C for 4 h, and finally calcined in a muffle furnace at 550°C for 4 h to obtain a catalyst carrier, recorded as TATY4.

[0073] Comparative Example 1

[0074] This comparative example provides a method for preparing a catalyst carrier, comprising the following steps:

[0075] The TiO2-Al2O3 composite oxide carrier in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 1:9, and then 2.5 wt% of sesbania powder by weight of the carrier, 0.5 wt% of nitric acid by weight of the carrier and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h, then dried in an oven at 120°C for 4 h, and finally calcined in a muffle furnace at 550°C for 4 h to obtain a catalyst carrier, recorded as TATY5.

[0076] Comparative Example 2

[0077] This comparative example provides a method for preparing a catalyst carrier, comprising the following steps:

[0078] The TiO2-Al2O3 composite oxide carrier in Example 1 and the Ti-doped Y molecular sieve in Example 2 were weighed and mixed evenly in a weight ratio of 19:1, and then 2.5 wt% of sesbania powder by weight of the carrier, 0.5 wt% of nitric acid by weight of the carrier and an appropriate amount of deionized water were added. After mixing evenly, the mixture was extruded into strips and aged at room temperature for 24 h, then dried in an oven at 120°C for 4 h, and finally calcined in a muffle furnace at 550°C for 4 h to obtain a catalyst carrier, recorded as TATY6.

[0079] Comparative Example 3

[0080] This comparative example provides a method for preparing an Al2O3 carrier by a precipitation method, comprising the following steps:

[0081] Weigh 37.5 g of aluminum nitrate nonahydrate and dissolve it in 1 L of deionized water to prepare 0.1 mol·L -1 To the aluminum nitrate solution, add an appropriate amount of dilute ammonia water drop by drop at 50°C while continuously stirring until the pH value is 7-8, continue stirring for 0.5h and then let stand for 2h, then cool to room temperature for vacuum filtration and washing operations, then place the solid product in an oven at 120°C and dry it for 4h, finally calcine the dried product at 550°C for 4h to obtain an Al2O3 carrier.

[0082] (II) Catalyst preparation

[0083] Example 7

[0084] This embodiment provides a method for preparing a hydrogenation catalyst using the TATY1 in the above embodiment 3, the TATY2 in the embodiment 4, the TATY3 in the embodiment 5 and the TATY4 in the embodiment 6 as a carrier, comprising the following steps:

[0085] The TATY1, TATY2, TATY3 and TATY4 composite carriers obtained above were crushed and sieved into particles of 20-40 mesh size. 7.6g of carrier particles were weighed and the water absorption was determined to be 1.3, then 1.92g of ammonium metatungstate and 2.34g of nickel nitrate hexahydrate were weighed and dissolved in 9.9g of deionized water and stirred evenly, and the Ni and W co-impregnation liquids were impregnated on the surface of each composite carrier by equal volume co-impregnation method, and dried naturally for 24h and placed in a 120℃ oven for 4h, and finally placed in a 550℃ muffle furnace for calcination for 4h to obtain hydrogenation catalysts, which were respectively recorded as NiW / TATY1, NiW / TATY2, NiW / TATY3 and NiW / TATY4.

[0086] Comparative Example 4

[0087] This comparative example provides a method for preparing a hydrogenation catalyst using the TATY5 in the comparative example 1, the TATY6 in the comparative example 2, the Al2O3 carrier in the comparative example 3, the carrier TA in the embodiment 1 and the carrier TY material in the embodiment 2 as a carrier, comprising the following steps:

[0088] The above-obtained TATY5, TATY6, Al2O3 carriers, TA and TY carriers were crushed and sieved into particles of 20-40 mesh size. 7.6g of carrier particles were weighed and the water absorption was determined to be 1.3, then 1.92g of ammonium metatungstate and 2.34g of nickel nitrate hexahydrate were weighed and dissolved in 9.9g of deionized water and stirred evenly, and the Ni and W co-impregnation liquids were impregnated on the surface of each carrier by equal volume co-impregnation method, and dried naturally for 24h and placed in a 120℃ oven for 4h, and finally placed in a 550℃ muffle furnace for calcination for 4h to obtain hydrogenation catalysts, which were respectively recorded as NiW / TATY5, NiW / TATY6, NiW / Al2O3, NiW / TA and NiW / TY.

[0089] (III) Performance characterization:

[0090] 1. Carrier pore properties

[0091] The pore properties of the carriers in Example 1, Example 2 and Comparative Example 3 were characterized, and the results are shown in Table 1.

[0092] Table 1

[0093]

[0094] 2. Catalyst acid properties

[0095] The acid properties of the catalysts in Example 7 and Comparative Example 4 were tested, and the test results are shown in Table 2.

[0096] Table 2

[0097]

[0098]

[0099] 3. Hydroprocessing evaluation

[0100] The catalysts in Example 7 and Comparative Example 4 were subjected to hydrogenation treatment evaluation. Specifically, 5 mL of the catalyst was placed in the constant temperature zone in the middle of the fixed bed high-pressure hydrogenation microreactor reactor, and the quartz sand of the same particle size was filled at the beginning and the end. The catalyst was sulfurized with a cyclohexane solution containing 2 wt% carbon disulfide as the sulfurizing liquid. The sulfurization method adopted a high and low temperature sulfurization method: first sulfurized at 320°C for 2h, and then sulfurized at 360°C for 4h. The hydrogen partial pressure and liquid hourly space velocity remained unchanged, which were 4MPa and 8h respectively.-1 .

[0101] After the vulcanization, Liaohe coking wax oil (nitrogen content 4465μg·g -1 , sulfur content is 3853μg·g -1 ) was used as the raw material to test the catalyst hydroprocessing performance. The reaction conditions were: temperature 380°C, hydrogen partial pressure 8MPa, hydrogen-to-oil volume ratio 1000:1, liquid hourly space velocity 1h -1 The catalyst samples after the reaction were taken for HRTEM characterization test, and the obtained active phase structure data are shown in Table 3. The results of the hydrogenation reaction of coker gas oil by each catalyst are shown in Table 4.

[0102] Table 3

[0103] catalyst Average lamella length, nm Average number of stacking layers W atomic dispersion NiW / TATY1 3.8 2.9 0.30 NiW / TATY2 4.0 2.8 0.29 NiW / TATY3 4.1 2.6 0.27 NiW / TATY4 4.3 2.4 0.26 NiW / TATY5 4.8 2.0 0.24 NiW / TATY6 3.9 2.9 0.26 <![CDATA[NiW / Al2O3]]> 4.1 2.0 0.28 NiW / TA 3.6 3.1 0.31 NiW / TY 4.2 2.3 0.26

[0104] Table 4

[0105]

[0106]

[0107] Combining the results in Table 2 and Table 3, it can be seen that as the content of Ti-doped Y molecular sieve increases, the catalyst The number of acid centers continues to increase, and the BAS / LAS value also continues to increase, but the average stacking number of active phases and the dispersion of active metal W gradually decrease, which means that the hydrogenolysis performance of the catalyst continues to improve, but the hydrogenation performance decreases. It can be further seen from the hydrogenation reaction results in Table 4 that with the increase of the content of Ti-doped Y molecular sieve, the catalyst's hydrogenation activity for coking wax oil first increases and then decreases. For the comparative example NiW / TY, due to the small pore size of its carrier, the accessibility of macromolecular nitrides / sulfides in coking wax oil to the active center is poor, so it shows a low denitrification rate / desulfurization rate. When the weight ratio of TiO2-Al2O3 composite oxide and Ti-doped Y molecular sieve is 9:1 to 6:4, the catalyst hydrogenation activity and hydrogenolysis activity are more suitable for the hydrogenation process of coking wax oil, achieving the matching of hydrogenation function and hydrogenolysis function, and showing higher denitrification and desulfurization activity for coking wax oil.

Claims

1. A catalyst carrier, wherein: It comprises titanium-aluminum composite oxide and Ti-doped Y molecular sieve; and the weight ratio of the titanium-aluminum composite oxide to the Ti-doped Y molecular sieve is 9:1-6:

4.

2. The catalyst carrier according to claim 1, wherein In the Ti-doped Y molecular sieve, the molar ratio of titanium to aluminum is 0.05 to 0.2:1 in the form of TiO2 and Al2O3.

3. The catalyst carrier according to claim 1 or 2, wherein In the titanium-aluminum composite oxide, the molar ratio of titanium to aluminum is 0.5 to 2:1 in the form of TiO2 and Al2O3.

4. A method for preparing a catalyst carrier according to any one of claims 1 to 3, wherein: include: The titanium-aluminum composite oxide, Ti-doped Y molecular sieve, binder, nitric acid and deionized water are mixed and then molded, subjected to a first aging, a first drying and a first calcination in sequence to obtain the catalyst carrier.

5. The preparation method according to claim 4, wherein: The temperature of the first drying is 50-120° C., and the time is 2-8 hours; the temperature of the first calcination is 450-600° C., and the time is 2-6 hours.

6. The preparation method according to claim 4, wherein The titanium-aluminum composite oxide is prepared by the following steps: Adding ammonia water to the first aluminum source aqueous solution until the pH of the system is 7-8, then adding a titanium aluminum co-solution containing the first titanium source and the second aluminum source to the system for reaction, and controlling the pH of the reaction to be 7-8 to obtain a sol system; The sol system is sequentially subjected to standing, first filtration, first washing, second drying, and second calcination to obtain the titanium-aluminum composite oxide.

7. The preparation method according to claim 4, wherein The Ti-doped Y molecular sieve is prepared by the following steps: Mixing a third aluminum source, a first silicon source, a first metal mineralizer and deionized water to obtain a directing agent; The directing agent, the second metal mineralizer and the second silicon source are first mixed, and then a dispersion containing a fourth aluminum source and a third metal mineralizer is added to the system, and then a fifth aluminum source and a second titanium source are added to the system to obtain a primary gel; The primary gel is subjected to a second aging and a first crystallization in sequence to obtain a secondary gel; The secondary gel, the fourth metal mineralizer and the third silicon source are mixed and then subjected to a second crystallization, a second filtration, a second washing, a third drying and a third calcination in sequence to obtain a primary molecular sieve; After the ammonium nitrate and the primary molecular sieve are mixed, a third crystallization, a third filtration, a third washing, a fourth drying and a fourth calcination are performed in sequence to obtain the Ti-doped Y molecular sieve.

8. A catalyst, wherein The invention comprises the catalyst carrier according to any one of claims 1 to 3 and an active metal component supported on the catalyst carrier.

9. The catalyst according to claim 8, wherein The active metal component is selected from Group VIB metal elements and / or Group VIII metal elements; based on 100% of the catalyst, the loading amount of the active metal component is 10-30wt%.

10. Use of the catalyst according to claim 8 or 9 in the hydrogenation treatment of inferior wax oil.

Citation Information

Patent Citations

  • Heavy petroleum fraction hydroprocessing catalyst and preparing method thereof

    CN106925287A